T Helper1/T Helper2 Cells and Resistance/Susceptibility to Leishmania Infection: Is This Paradigm Still Relevant? - Alexander, James; Brombacher, Frank (Frontiers in Immunology, 2012)
Work in large part on Leishmania major in the 1980s identified two distinct apparently counter-regulatory CD4+ T cell populations, T helper (h)1 and Th2, that controlled resistance/susceptibility to infection respectively. However, the generation of IL-4-/- mice in the 1990’s questioned the paramount role of this Th2 archetypal cytokine in the non-healing response to Leishmania infection. The more recent characterisation of CD4+ T cell regulatory populations and further effector CD4+ T helper populations (Th17) (Th9) and (T follicular (f)h cells) as well as the acknowledged plasticity in T helper cell function has further added to the complexity of host pathogen interactions. These interactions are complicated by the multiplicity of cells that respond to CD4+ T cell subset signatory cytokines, as well as the diversity of Leishmania species that are often subject to significantly different immune-regulatory controls. In this article we review current knowledge with regard to the role of CD4+Tcells and their products during Leishmania infection. In particular we update on our studies using conditional IL-4Rα gene deficient mice that have allowed dissection of the cell interplay dictating the disease outcomes of the major Leishmania species infecting humans.